Concept of Uslub Amr in the context of prayer in surah Al-Baqarah - Syakirah Rifa’in@Mohd Rifain,; Mat Taib Pa, (Penerbit Universiti Kebangsaan Malaysia, 2022)
This study discusses the uslub amr in surah al-Baqarah. This research has two main objectives whereby the first is to identify the form and reason of amr in surah al-Baqarah, and the second, to summarize the implied message of the amr form in the context of prayer in surah al-Baqarah. This is a qualitative study of text analysis based on sentence context using related commentary (tafsir) from past and modern scholar. The first research objective is based on the ‘Abbas (1997) Theory whereas the second research objective is based on opinions of al-Awsiy (1988) Theory. The findings of this study indicate that there are eight verses which relate to prayer that overall, there is one form of amr which is fi‘l amr. For amr, there are four purposes namely compulsory (wajib), al-irsyad (guidance), al-nadb (sunna) and al-dawan (continuance). For implied messages used in amr form, it involves one form of amr in the context of prayer which is fi‘l amr that is used as a firm and strong command to explain main and basic things. In conclusion, the various forms of amr that is used in a certain context has implied messages.